Determining prognostic factors and optimal surgical intervention for early-onset triple-negative breast cancer - Zheng, Yi-Zi; Liu, Yan; Deng, Zhen-Han; Liu, Guo-Wen; Xie, Ni (Frontiers in Oncology, 2022)
Background: Few studies have focused specifically on prognostic factors and optimal surgical intervention for early-onset triple-negative breast cancer (eTNBC), which is characterized by high malignancy and poor prognosis. Methods: We performed a cohort study with a median follow-up of 31 months using Surveillance, Epidemiology, and End Results (SEER) data of patients diagnosed with stages I–III eTNBC between 2010 and 2016. In addition, we collected cases between 2006 and 2016 from our center as an external validation set. Clinical features, pathologic characteristics and oncologic outcomes were analyzed. Prognostic factors for overall survival (OS) and breast cancer-specific survival (BCSS) were determined by Cox proportional hazards analyses and were incorporated into the prognostic nomogram. Subgroup analysis based on propensity score matching method was conducted to explore the subset of patients that would benefit from breast-conserving therapy (BCT). Results: Based on SEER dataset, patients with eTNBC were more likely to undergo mastectomy than BCT. On multivariable analysis, patients with better survival outcomes were those not married, uninsured, had higher T and N stage, and had histological type of mixed invasive ductal and lobular carcinoma. The prognostic nomogram based on these variables successfully predicted the 3- and 5-year BCSS (C-index in training cohort, 0.774; in validation cohort from SEER, 0.768; in validation cohort from our center, 0.723). Subgroup analysis illustrated that patients with T1N0M0 or T2-4N+M0 tumors who underwent BCT achieved longer overall survival than those who underwent mastectomy (for T1N0M0, P = 0.022; for T2-4N+M0, P = 0.003); however, the type of surgery did not influence OS among patients with T1N+M0 or T2-4N0M0 tumors (for T1N+M0, P = 0.305; for T2-4N0M0, P = 0.317). Conclusions: The prognosis of patients with eTNBC is mainly affected by marital status, insurance status, T stage, N stage and histological type. The prognostic nomogram based on these factors is quite reliable. Subgroup analysis suggested that BCT may be a superior option for patients with eTNBC, especially those with T1N0M0 and T2-4N+M0 tumors.